Flexible and scalable participatory syndromic and virological surveillance for respiratory infections: Our experiences in The Netherlands - Tara Smit; Gesa Carstens; Wanda Han; Kirsten Bulsink; Jordy de Bakker; Mansoer Elahi; Rianne van Gageldonk-Lafeber; Susan van den Hof; Dirk Eggink; Albert Jan van Hoek (PLoS ONE, 2025)
Background During the COVID-19 pandemic participatory digital surveillance of symptoms (syndromic surveillance) re-established itself as a worthy addition to the surveillance pyramid, as they are scalable, flexible and function independent from the health care system or health care seeking behaviour. A limitation of syndromic surveillance however is the inability of pathogen identification. We describe our experiences regarding integrating self-swabs with centralized testing into a participatory syndromic surveillance system in the Netherlands (Infectieradar). Methods In the 2022/2023 winter season Infectieradar was extended to include nose- and throat swabs. Participants received test-kits including SARS-CoV-2 antigen tests for home use as well as nose- and throat swabs. All SARS-CoV-2 positive participants and a random sample of symptomatic SARS-CoV-2 self-test negative participants were asked to return a nose- and throat swab by regular post. Self-test negative swabs were tested by multiplex-PCR on 22 pathogens, including SARS-CoV-2. Self-test SARS-CoV-2 positive samples with a Ct-value < 30 were sequenced for variant analysis. Results Over 17,000 participants were included in the study, which involved relatively older persons and relatively more women compared to the general Dutch population. We collected 1,475 (median: 37 per week) swabs from participants with positive and 4,096 swabs (median: 136 per week) from participants with negative SARS-CoV-2 antigen self-tests (74% of those who requested to send in a swab). Of the swabs following a negative self-test, 47.7% tested positive in the multiplex-PCR, with rhinovirus/enterovirus being the most frequently detected pathogen (24.5%). Self-test SARS-CoV-2 positivity was laboratory-confirmed in 96.1% of swabs and showed parallel variant distributions as the national SARS-CoV-2 variant surveillance. Conclusion This large-scale, centralized participatory surveillance system provides a comprehensive approach for performing syndromic and virological surveillance in the general population, including respiratory pathogen detection by self-test or multiplex-PCR. Despite the non-representative sample it was possible to monitor the variant distribution. Given the continuous collection of samples among those who don’t seek care, the system provides valuable insights into circulating respiratory pathogens and is part of an answer on how to study the transmission, competition, virulence and evolution of circulating pathogens in interpandemic periods.